Somatoform Dissociative Symptoms Have No Impact on the Outcome of Trauma-Focused Treatment for Severe PTSD - Harmen A. Zoet (Journal of Clinical Medicine, 2021)
For patients with complex or other severe forms of PTSD, particularly in cases with dissociative symptoms, different treatment approaches have been suggested. However, the influence of somatoform dissociation on the effectiveness of trauma-focused treatment has hardly ever been studied. This study aims to test the hypotheses that (1) PTSD patients reporting a low level and those reporting a high level of somatoform dissociative symptoms would both benefit from an intensive trauma-focused treatment, and that (2) somatoform dissociative symptoms would alleviate. Participants were 220 patients with severe PTSD, enrolled in an intensive treatment program combining EMDR therapy and prolonged exposure therapy, without a preceding stabilization phase. Trauma history was diversified, and comorbidity was high. PTSD symptoms (CAPS-5 and PCL-5) and somatoform dissociative symptoms (SDQ-5 and SDQ-20) were assessed at pre-treatment, post-treatment and at six months after completion of treatment. The course of both PTSD and somatoform dissociative symptoms was compared for individuals reporting low and for those reporting high levels of somatoform dissociative symptoms. Large effect sizes were observed regarding PTSD symptoms reduction for patients with both low and high levels of somatoform dissociation. Somatoform dissociation did not impact improvement in terms of PTSD symptom reduction. The severity of somatoform dissociative symptoms decreased significantly in both groups. This decrease was greater for those with a positive screen for a dissociative disorder. These results add further support to the notion that the presence of strong somatoform dissociative symptoms in patients with PTSD does not necessarily call for a different treatment approach. Clinical implications are discussed.